Learning Model of Al-Islam and Integrative Muhammadiyah for Students at MTs Muhammadiyah Aimas - Budi Santoso; Muhkhlas Triono; Muhammad Muzakki; Lestari Lestari; Jaharudin Jaharudin (ISTAWA, 2023)
The development of Muhammadiyah in West Papua is marked by the development of Muhammadiyah's charitable endeavors in the field of education. Where several Muhammadiyah schools are excellent for the people of Sorong, both Muslims and non-Muslims. One of the Muhammadiyah educational institutions that is of interest to the Muslim community is MTs Muhammadiyah II Aimas. The aim of the research is to analyze the learning model of al-Islam and integrative Muhammadiyah and learning implementation. The research paradigm is interpretive, qualitative approach, type of case study research, data collection techniques are carried out by observation, interviews, and documentation. The resulting data were analyzed using a descriptive model with the following steps: data collection, data condensation, data presentation, and conclusions. In order for the validity of the data to be accounted for, the following measures are carried out: extending the observation period, continuous observation, triangulation, and conducting member checks. The conclusion from the results of this study is that the implementation of Al-Islam and Kemuhammadiyahan learning at MTs Muhammadiyah Aimas is divided into two, namely Islamic Religious Education and Al-Islam and Kemuhammadiyahan. Learning is implemented with Islamic activities contained in extracurricular activity programs, namely Hisbul Wathan, Drum Band, Tapak Suci, Dhuha Prayer and Tahsin. The integrative AIK learning model referred to in this study is in line with Fogarty's (1991) theory, namely The Integrated Model (integrative model). that is integrating one discipline. By focusing on integrating a number of skills that the teacher wants to train his students, including thinking skills, social skills, and organizational skills.